The colonial species bird nesting near Ukrainian Antarctic station Academic Vernadsky (the season 2010-2011 years) - D. V. Pilipenko (Ukrainian Antarctic Journal, 2013)
During 15 Ukrainian Antarctic expeditions, since March 23 2010 on March 26 2011, in region Ukrainian Antarctic station Academic Vernadsky was conducted study avifauna region. Special attention was to give consideration colonial type of the birds nesting here. In region is noted four such type: Gentoo Penguin (Pygoscelis papua (J.R.Forster, 1781)), Adelie Penguin (Pygoscelis adeliae (Hombron & Jacquinot, 1841)), Chinstrap Penguin (Pygoscelis antarctica (J.R.Forster, 1781)) and Antarctic Shag (Phalacrocorax atriceps (syn bransfieldensis) Murphy, 1936). Within under investigation territory, which has covered more than 1000 km², commencing from island Booth on north and cape Perez in the south, and width about 10 km, along seaside of the Antarctic peninsula including island of the Roca and Cruls, was discover more than ten places nesting these species. Except already known, were discovered and several earlier not described colony on Antarctic peninsula, including the most south, on declivity of the mountain Demaria with coordinate 65º16´160" south latitude and 64º07´316" west longitude.  The total number nesting birds have amount more than 12000 pairs, including more than 8000 pairs of the Gentoo Penguin, more than 3000 pairs of the Adelie Penguin, slightly more 20 pairs of the Chinstrap Penguin and about 200 pairs of the Antarctic Shag.